Pulmonary Vascular Resistance Estimated by Echocardiography in Dogs With Myxomatous Mitral Valve Disease and Pulmonary Hypertension Probability - Suzuki, Ryohei; Yuchi, Yunosuke; Kanno, Haruka; Saito, Takahiro; Teshima, Takahiro; Matsumoto, Hirotaka; Koyama, Hidekazu (Frontiers in Veterinary Science, 2021)
Post-capillary pulmonary hypertension (PH) is a life-threatening complication in dogs with myxomatous mitral valve disease (MMVD). An increase in pulmonary vascular resistance (PVR) is associated with post-capillary PH progression. In humans, PVR estimated by echocardiography (PVRecho) enables the non-invasive assessment of PVR in patients with PH. This study aimed to evaluate the clinical utility of PVRecho in dogs with MMVD, PH probability, and right-sided congestive heart failure (R-CHF). Dogs with MMVD and detectable tricuspid valve regurgitation were included in the study. Dogs were classified into three PH probability groups (low/intermediate/high) and according to the presence or absence of R-CHF. All dogs underwent echocardiographic measurements for right ventricular (RV) morphology and function. PVRecho was calculated by two methods using tricuspid valve regurgitation velocity and velocity–time integral of the pulmonary artery flow (PVRecho and PVRecho2). RV size indicators were significantly higher with a higher probability of PH. RV strain and velocity–time integral of the pulmonary artery flow in the high probability group were significantly lower than those in the other groups. Tricuspid valve regurgitation velocity, PVRecho, and PVRecho2 were significantly higher with an increase in PH probability. Logistic regression analysis revealed a significant association between the presence of R-CHF and increased PVRecho2 and end-diastolic RV internal dimension normalized by body weight. PVRecho and PVRecho2 showed significant differences among the PH probability groups. These non-invasive variables may be useful for the diagnosis and stratification of PH and the determination of the presence of R-CHF in dogs with MMVD.